2019
DOI: 10.1021/acs.biomac.9b01198
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Removal of Cu2+ in Water by Carboxymethylated Cellulose Nanofibrils: Performance and Mechanism

Abstract: Simultaneous production and functionalization of cellulose nanofibrils (CNFs) for heavy metal ion removal is an economical and promising solution to expedite their use in water treatment. In this work, carboxymethylated CNFs (CMCNFs) with a carboxylate content up to 2.7 mmol/g are prepared by a combination of carboxymethylation and homogenization, which show diameters of 3.40–3.53 nm and lengths of 1210.6–383.3 nm. The effect of experimental conditions (including pH, carboxylate content, contact time, initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 67 publications
(80 reference statements)
1
27
0
Order By: Relevance
“…from wastewater. [ 72,156–158,228,230–233 ] The removal of heavy metal ions using wood‐based filter is particularly attractive, especially when the concentration of the heavy metal ions is low. [ 228 ] Although removing heavy metal ions from contaminated water has been demonstrated by various techniques, it remains challenging for treating wastewater with trace amount of heavy metal ions.…”
Section: Applications In Various Emerging Devicesmentioning
confidence: 99%
“…from wastewater. [ 72,156–158,228,230–233 ] The removal of heavy metal ions using wood‐based filter is particularly attractive, especially when the concentration of the heavy metal ions is low. [ 228 ] Although removing heavy metal ions from contaminated water has been demonstrated by various techniques, it remains challenging for treating wastewater with trace amount of heavy metal ions.…”
Section: Applications In Various Emerging Devicesmentioning
confidence: 99%
“…The functionalization of CNFs can promote the applications of CNF-based nanomaterials in water purification, which attracted increasing attention recently. Qin and co-workers produced carboxymethylated CNFs, which could be applied to transfer the Cu 2+ -polluted water into drinking water directly [ 15 ], indicating their high adsorption ability to Cu 2+ ( Figure 5 b). In a similar study, Hong et al proposed the design of a modular adsorbent by embedding carboxymethylated CNFs in polyurethane foam, which combined the unique adsorption properties of both CNFs and polymer foam to achieve a superior high adsorption capacity and excellent recyclability [ 14 ].…”
Section: Environmental Science Applicationsmentioning
confidence: 99%
“…Reprinted with permission from Ref. [ 15 ], Copyright 2019, American Chemical Society. ( c ) Wood-derived CNFs for the removal of Cu 2+ .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, the high number of hydroxyl groups on the surface of cellulose bers can provide a platform to modify it with different properties. Qin et al (2019a) showed that its adsorption capacity for Cu 2+ decreased from 68mg/g to 45mg/g after 4 cycles.…”
Section: Nanocellulose Based Adsorbents For Cu 2+ Removalmentioning
confidence: 99%